20 Minute Manager Series: Virtual Collaboration - Harvad Business Review (Harvard Business Review Press, 2016)
This book will help you build productive relationships with colleagues while you foster your own sense of initiative-no matter where you are. It walks you through these important basics: - Working productively from any location. - Picking the right tools for wherever you're working, at home or on the road. - Clarifying the roles, tasks, and processes that will govern your collaboration. - Communication effectively over a variet of media. - Getting and keeping your colleagues' attention when you're not in the same place. - Setting-and sticking to-a schedule that works for both you and your dispersed collabrators. - Keeping isolation at bay by connecting with your coworkers.